Non-coronary sinus of Valsalva aneurysm diagnosed after a road traffic accident - Ribeiro, A (1999)
A 38 year old man with a huge unruptured sinus of Valsalva aneurysm, complicated with severe valvar aortic regurgitation, is described. The aneurysm was detected by echocardiography in the asymptomatic patient who presented with an intense precordial diastolic rumble after a road traffic accident. The patient had successful surgery for the aneurysm and aortic valve replacement. Possible aetiologies for the aneurysm and a brief revision of clinical aspects and treatment are discussed.